Some features of bypass engine operation process with separate exhaust nozzles - V. V. Medvedev; V. T. Shulekin (Научный вестник МГТУ ГА)
In the article some equations are derived to establish the relationships between the thermodynamic cycle parameters applying to bypass engines with separate exhaust nozzles. Necessary calculations are made and the main dependences are analyzed. Some of them have not been analyzed in the famous articles.